ISLAMIC CHARACTER EDUCATION VALUES IN MANDAILING AND ANGKOLA COMMUNITIES IN NORTH SUMATERA PROVINCE - Rahmat Hidayat; Tien Rafida (State Islamic University of North Sumatra Indonesia, 2019)
Mandailing and Angkola culture are a culture that combines Islamic traditions and religions or is known as